Knowledge of use and type of references in Library and Information Science and Legal Medicine as support for specialized librarians. (September 2019) - Nieto-Pino, Nerea; Faba-Pérez, Cristina; Gómez-Crisóstomo, Rocío
Librarians of specialized institutions need to have solid knowledge of the scientific environment (impact of publications, use of citations and scientific references, etc.) related to the group for which they work in order to properly manage the collection of their libraries. The present research analyses the evolution of the use and types of references cited by academics in Library and Information Science and in Legal Medicine as an aid for specialist librarians in this sense. The study has a dual aspect: one is to determine how the behaviour of references, especially Web references, in relation to accessibility and use has evolved over 15 years in alternating periods (1999, 2004, 2009, 2013) in these two areas, and the other is to determine from the type of references scientists of prestige use in their publications whether they consider the Internet to be a reliable source of information for their research. Two journals with high impact factors according to Journal Citation Reports were selected from each category: Journal of the American Society for Information Science & Technology (JASIST) and Information Processing & Management (IP&M) corresponding to Information Science, and Regulatory Toxicology & Pharmacology (RT&P) and Forensic Science International (FSI) corresponding to Legal Medicine. The results showed greater accessibility and use of Web references in the Information Science community, but also considerable progress in these aspects in recent years in Legal Medicine.